2015
DOI: 10.2106/jbjs.n.00503
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Fixation Improves Outcomes of Spinal Fusion for C1-C2 Instability in Children with Skeletal Dysplasias

Abstract: The nonunion rate is relatively high after patients undergo spinal fusion for C1-C2 instability with nonrigid instrumentation, even if a halo-body jacket is applied. Rigid fixation with screws and rods improves fusion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 28 publications
1
18
0
1
Order By: Relevance
“…In accordance with previous studies, we have noted that rigid fixation enhances fusion rates. 5 - 7 Like Crostelli et al 30 we have found that rigid adult instrumentation can be used to treat pediatric cervical spine instability. Similarly, the anatomical dimension rather than age is the most decisive factor when planning fixation, although sometimes challenging to perform.…”
Section: Discussionmentioning
confidence: 90%
“…In accordance with previous studies, we have noted that rigid fixation enhances fusion rates. 5 - 7 Like Crostelli et al 30 we have found that rigid adult instrumentation can be used to treat pediatric cervical spine instability. Similarly, the anatomical dimension rather than age is the most decisive factor when planning fixation, although sometimes challenging to perform.…”
Section: Discussionmentioning
confidence: 90%
“…Most studies on the outcomes of cervical spinal fusion in patients with SEDC have included both children and adults or other skeletal dysplasias. 8,10,12 Ain et al 12 retrospectively identified 25 patients age ranging 1.75 to 46.9 years with various skeletal dysplasias who underwent surgery for cervical instability. Of those patients, 4 of 7 SEDC patients were children; ages ranging 21 to 89 months with mean 58 months follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 Several studies have shown the results of a small number of upper cervical fusions in patients with SEDC. [8][9][10] However these studies included children and adults with many forms of spondyloepiphyseal dysplasia and other skeletal dysplasias. Literature to date has not well-documented the long-term results and complications of this population.…”
mentioning
confidence: 99%
“…The complications in the screw cohorts, including transient neurological deficit, cerebrospinal fluid leak, kyphotic deformity, infection, and nonunion, appeared to be less severe than those in the wire cohorts, which had complications including death, respiratory compromise, and quadriparesis. However, a few studies reported iatrogenic vertebral artery injury or dural venous sinus injury by applying cervical or occipital screw constructs to the smaller and thinner bone structure [18][19][20] , which might result in mortality. Regarding vertebral artery variations, only 1 patient with bilateral vertebral arteries entering the transverse foramen at the C4 level was observed in this series.…”
Section: Fusion Rates and Complications Related To Fusion Surgery In mentioning
confidence: 99%